Acute withdrawal after bremazocine and the interaction between mu- and kappa-opioid receptors in isolated gut tissues. - Valeri, P (1995)
1. This study was undertaken to investigate whether, after a brief exposure of guinea-pig isolated ileum and rabbit jejunum to bremazocine, a kappa-opioid agonist also possessing antagonist activity at mu-opioid receptors, the addition of opioid antagonists produced withdrawal contractures. Our aim was to verify in these tissues the existence of an interaction between the mu- and kappa-opioid systems. 2. In guinea-pig ileum preparations previously exposed for 5 min to bremazocine at 5.7 x 10(-7) M and 5.7 x 10(-8) M, naloxone (5 x 10(-7) M) elicited no response whereas in tissues exposed to a lower bremazocine concentration (5.7 x 10(-9) M), naloxone (5 x 10(-7) M) and the selective kappa-opioid antagonist, nor-binaltorphimine (3.4 x 10(-8) M) both produced a strong contracture. 3. Bremazocine (5.7 x 10(-7) M) administered to guinea-pig isolated ileum, previously exposed for 5 min to morphine (10(-7) M), induced a withdrawal contracture. In contrast, lower bremazocine concentrations (1.4 and 7.1 x 10(-8) M) did not elicit a withdrawal contracture. 4. Naloxone (5 x 10(-7) M), added to the bath after a 5 min exposure of guinea-pig ileum to morphine (10(-7) M), elicited the characteristic withdrawal contracture. Bremazocine (1.4-7.1 x 10(-8) M) added 1 min before naloxone (5 x 10(-7) M) inhibited the naloxone withdrawal contracture in a dose-related way whereas naloxone 5 x 10(-8) M added 1 min before naloxone 5 x 10(-7) M, did not affect the withdrawal response.(ABSTRACT TRUNCATED AT 250 WORDS)